Impact of a Bacillus Direct-Fed Microbial on Growth Performance, Intestinal Barrier Integrity, Necrotic Enteritis Lesions, and Ileal Microbiota in Broiler Chickens Using a Laboratory Challenge Model - Hernandez-Patlan, Daniel; Solis-Cruz, Bruno; Pontin, Karine Patrin; Hernandez-Velasco, Xochitl; Merino-Guzman, Ruben; Adhikari, Bishnu; López-Arellano, Raquel; Kwon, Young Min; Hargis, Billy M.; Arreguin-Nava, Margarita A.; Tellez-Isaias, Guillermo; Latorre, Juan D. (Frontiers in Veterinary Science, 2019)
Decreases in the use of antibiotics and anticoccidials in the poultry industry have rise the appearance of necrotic enteritis (NE). The purpose of this study was to evaluate the effect of a Bacillus direct-fed microbial (DFM) on growth performance, intestinal integrity, NE lesions and ileal microbiota using a previously established NE-challenged model. At day-of-hatch, chicks were randomly assigned to three different groups: Negative control (NC), Positive control (PC) challenged with Salmonella Typhimurium (day 1), Eimeria maxima (EM, day 13) and Clostridium perfringens (CP, day 18-19), and Bacillus-DFM group (DFM) challenged as the PC. Body weight (BW) and body weight gain (BWG) were measured weekly. Total feed intake (FI) and feed conversion ratio (FCR) were evaluated at day 21. Liver samples were collected to assess bacterial translocation and blood samples were used to measure superoxide dismutase (SOD) and fluorescein isothiocyanate-dextran (FITC-d). Intestinal contents were obtained for determination of total IgA and microbiota analysis. NE lesion scores (LS) were performed at day 21. Chickens consuming the DFM significantly improved BW and had a numerically more efficient FCR compared to PC at day 21. Additionally, there were no significant differences in FCR between the DFM group and NC. Furthermore, the DFM group showed significant reductions in LS, IgA and FITC-d levels compared to the PC. However, there were no significant differences in SOD between the groups. The microbiota analysis indicated that the phylum Proteobacteria was significantly reduced in the DFM group in comparison to PC. At the genus level, Clostridium, Turicibacter, Enterococcus, and Streptococcus were reduced, whereas, Lactobacillus and Bacillus were increased in the DFM group as compared to PC (p < 0.05). Likewise, the DFM significantly reduced CP as compared to PC. In contrary, no significant differences were observed in bacterial composition between NC vs DFM. In addition, beta diversity showed significant differences in the microbial community structure between NC vs PC, and PC vs DFM. These results suggest that the dietary inclusion of a selected DFM could mitigate the complex negative impacts caused by NE possibly through mechanism(s) that might involve modulation of the gut microbiota.